The Influence of Brand Image, Service Quality, and Price on Damri Service Users at Plaza Medan Fair - Ricky Rafii Ritonga; Elsa Afriyanti; Endrian Ujiati Rahayu; Angga Rizki Pratama (Enrichment : Journal of Management, 2022)
Brand image is the public's response to a company or product. A good image will benefit the company, because customers subconsciously recommend it to others. Damri buses are known to have a good reputation and their names are easy to remember among the public. Damri is a brand mark of a BUMN that until now has carried out its function as a service provider for the transportation of people and goods. Building a brand image is important for business companies. Brand is not just a name or a symbol. Brand is a differentiator of a product with other products. In this case, the competition between transportation services in the city of Medan is getting tighter because there are many buses so that a strong brand image is needed in order to foster a back impression among bus customers. The purpose of this study was to determine the effect of brand image on community user satisfaction in Medan City partially on Perum Damri transportation services and to determine the effect of service quality on community user satisfaction in Medan City partially on Perum Damri transportation services. Knowing the effect of price on user satisfaction in the city of Medan partially on Perum Damri transportation services. The results of the test simultaneously obtained a value of 67.068 > 3.09 and a significant probability value of 0.000 < 0.05. The coefficient of determination test shows that 66.7%, namely brand image, service quality and price have an impact on user satisfaction.